Clients Satisfaction of a Community Clinic in Rural Bangladesh - Sonia Akber Moon; Baizid Khoorshid Riaz; Md Sajidul Huq; Farzana Akter; Tamsasul Farha; Mohammad Nurunnabi (KYAMC Journal, 2025)
Background: The community clinic (CC) is a vital component of rural healthcare in Bangladesh, extending primary health services to remote areas. Objective: To assess the client’s satisfaction regarding the health services of a community clinic in rural Bangladesh. Materials and Methods: This cross-sectional study was conducted at Boali Community Clinic, located in the Kaligonj upazila of Gazipur, Bangladesh. A total of 140 respondents were included in this study, and a convenience sampling technique was employed. Data were collected using a pre-tested semi-structured questionnaire through face-to-face interviews. Results: The majority of the respondents (48.4%) fell into the 18-30 age group, with a mean age of 33.6 years and a standard deviation of ±10.8 years. Most of the respondents (73.4%) were females, 91.4% identified as Muslims, and 92.1% were married. About 9.3% of the respondents were illiterate, while the remaining 90.7% were literate. More than half of the respondents (68.6%) were homemakers. 70.6% of the respondents visited the community clinic for the treatment of minor ailments, 20.9% for maternal and child health services, and 6.5% for the diagnosis of non-communicable diseases (NCD) and complicated illnesses. In terms of satisfaction levels, the study revealed that 54.4% of the respondents were moderately satisfied with the services of the community clinic, while 30.7% reported high satisfaction, and 15.0% expressed mild satisfaction. The level of satisfaction with community clinic services was significantly associated with the marital status of the respondents (p=0.026) and showed a near-significant association with the type of house where respondents lived (p=0.005). Monthly income was also found to be correlated with the satisfaction score (p=0.001). Conclusion: The study highlighted certain areas of improvement, including addressing infrastructure issues and expanding specialized healthcare services. The findings underscore the importance of continuous enhancements to community clinics, ultimately benefiting the rural population in Bangladesh. KYAMC Journal. 2024; 15(02): 88-93